معاشی خود کفالت کا اسلامی تصور (Al-Qamar, 2023)
Prophet Muhammad (peace be upon him) stated that the best earnings are those earned through one's own efforts. In this regard he cited the example of the Prophet David, who used to earn his livelihood with his own hands. Quran emphasizes the concept of self-sufficiency in the verse: "Was not the earth of Allah spacious enough for you to emigrate therein?" (Quran 4:97). Prophet’s companions, including Abu Bakr and Umar (may Allah be pleased with them), continued his practicing his teacings and deeds. Concept of migration is not solely about physically moving from one place to another; it also encompasses the idea of actively working for one's livelihood. Prophet Muhammad (peace be upon him), the best of all creation, engaged in trade to support himself and his family. He set an example for his followers by emphasizing the value of earning a living through honest labor. This paper argues that Islam encourages self-sufficiency and discourages dependency on others, as evidenced by the teachings and actions of the Prophet Muhammad (peace be upon him) and his companions. By adhering to these principles, societies can achieve economic stability and eradicate poverty, ultimately fostering a prosperous and pleasant community.
Keywords: Economics; self-sufficiency; Islam